Carbon nanotubes: a review on green synthesis, growth mechanism and application as a membrane filter for fluoride remediation. Issue 4 (2nd October 2021) - Chufa, Bayisa Meka; Murthy, H. C. Ananda; Gonfa, Bedasa Abdisa; Anshebo, Teketel Yohannes
ABSTRACT: In most African rural communities, ground water is the primary source of drinking water. Fluoride is a harmful substance found in ground water that causes serious health problems. The only answer to the fresh and clean water crisis is water treatment. Sustainable, cost-effective and efficient membrane filtration technologies are becoming progressively vital to solve the scarcity. Owing to their unique tunable physico-chemical properties, carbon nanotubes (CNTs) were used in water treatment. This paper thoroughly reviews the health effects of consuming excess fluoride ions. The recent progress on the synthesis of CNT was also highlighted. A special emphasis was given to green synthetic routes for its preparation. Green catalysts provide defined size and morphology than conventional materials and also prevent metal leaching. The effects of incorporation of CNTs as filler in the matrix have been discussed in detail. The large-scale production of CNTs and their growth mechanisms; for water purification purposes are explored. It has been observed that CNTs have got an excellent filtration performance of fluoride, low biofouling activities and high water flux capacity. Besides, this review attempt to provide a clue for the functionalized CNTs based membranes as potential solutions in water purifications of fluoride ions in the future. GRAPHICAL ABSTRACT: UF0001